HORMONAL RESPONSE TO DIFFERENT REST INTERVALS DURING RESISTANCE TRAINING WITH LIGHT LOADS - Payam Mohamad-Panahi; Hadi Rohani; Navid Lotfi (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: The purpose of the present study was to determine the appropriate rest time between sets during weight training with light load. Material: Seventeen cadet wrestlers (age =16.7В±0.6 yrs.; height =169.2В±8.2 cm; and weight =51.4В±7.9 kg) were recruited from wrestling clubs in the Iranian province of Kurdistan and served as subjects in this study. This study was conducted over seven sessions with 48 hours recovery between sessions. In the first session, the characteristic features of subjects were recorded and the one repetition maximum in the bench press test was determined for each subject. On 6 separate occasions, subjects performed a 4 set of bench press at 60% 1RM with a 90 and 240 seconds rest interval until volitional fatigue. The numbers of repetition performed by the subjects, and also, cortisol and testosterone levels and 1RM were recorded. The results showed that there was a significant difference in the sustainability of repetitions during 4 sets bench press with 60 % load between 90 and 240 seconds rest intervals (rest interval effect) (p<0.05) as well as with 90% load. Results: Additionally, there was a significant difference in the sustainability of repetitions during 4 sets bench press in 90 and 240 seconds rest intervals, both, between light and heavy loads (load effect). Plasma cortisol concentrations significantly increased after all bench press trials. Also, the rest interval effect was statistically significant in both 60 % and 90% load trials. But, the load effect was only statistically significant in 90 seconds rest interval trial (p<0.05). In contrast, plasma testosterone concentrations significantly increased after 4 sets bench press only in 90 seconds rest interval with heavy load and 240 seconds rest interval with light load (p<0.05). Accordingly, testosterone to cortisol (T:C) ratio were significantly decreased after 4 sets bench press in 90 seconds rest interval with light load and 240 seconds rest interval with heavy load. Also, load effect was statistically significant only in 90 seconds rest interval trials and rest interval effect was statistically significant only in heavy load trials (p<0.05). Conclusions: Based on these results it can be concluded that when resistance training with light loads, higher resting interval (240 seconds) may be provides a better anabolic environment for muscle growth and keep the training intensity.